Advancements and Challenges in Potassium Ion Batteries: A Comprehensive Review. (31st January 2020) - Rajagopalan, Ranjusha; Tang, Yougen; Ji, Xiaobo; Jia, Chuankun; Wang, Haiyan
Abstract: Demand for energy in day to day life is increasing exponentially. However, existing energy storage technologies like lithium ion batteries cannot stand alone to fulfill future needs. In this regard, potassium ion batteries (KIBs) that utilize K ions in their charge storage mechanism have attracted considerable attention due to their unique properties and are therefore established as one of the future battery systems of interest among the scientific community. Nevertheless, the development and identification of appropriate electrode materials is very essential for practical applications. This review features the current development in KIBs electrode and electrolyte materials, the present challenges facing this technology (in the commercial aspect), and future aspects to develop fully functional KIBs. The potassium storage mechanisms, evolution of the KIBs, and the advantages and disadvantages of each category of materials are included. Additionally, various approaches to enhance the electrochemical performances of KIBs are also discussed. This review is not only an amalgamation of different viewpoints in literature, but also contains concise perspectives and strategies. Moreover, the potential emergence of a novel class of K‐based dual ion batteries is also analyzed for the first time. Abstract : The development and identification of appropriate electrode and electrolyte materials is very essential for practical potassium ion storage applications. Hence, an understanding of the current development in potassium‐based electrode and electrolyte materials and the present performance challenges is critical.